Epidemiological study (2006–2012) on the poisoning of small animals by human and veterinary drugs. (1st March 2014) - Caloni, F.; Cortinovis, C.; Pizzo, F.; Rivolta, M.; Davanzo, F.
Abstract : A retrospective study was conducted on the exposure of dogs and cats to drugs, reported to the Poison Control Centre of Milan (Centro Antiveleni di Milano (CAV)) between January 2006 and December 2012. Calls related to drugs for human use and veterinary drugs accounted for 23.7 per cent of total inquiries (1415) received by CAV and mostly involved dogs (70 per cent of enquiries). Exposure to drugs for human use accounted for 79 per cent of cases involving dogs, whereas veterinary drugs were the main culprit (77 per cent) in the case of cats. The most common class of drugs for human use proved to be CNS drugs (26.8 per cent), followed by NSAIDs (19.6 per cent) and cardiovascular and endocrine drugs (12.9 per cent each). The majority of calls (95.2 per cent) related to veterinary drugs involved dogs and cats exposed to parasiticides. The outcome was reported in only 58.2 per cent of cases, and fatal poisoning accounted for 8.7 per cent of these cases. Epidemiological data from this Italian survey provide useful information on animal exposure to drugs. The knowledge of agents involved in poisoning episodes can help veterinarians make the correct diagnosis and institute preventive measures to possibly reduce animal exposure to drugs.